2010
DOI: 10.1007/s00425-010-1337-0
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis thaliana transcriptional co-activators ADA2b and SGF29a are implicated in salt stress responses

Abstract: The transcriptional co-activator ADA2b is a component of GCN5-containing complexes in eukaryotes. In Arabidopsis, ada2b mutants result in pleiotropic developmental defects and altered responses to low-temperature stress. SGF29 has recently been identified as another component of GCN5-containing complexes. In the Arabidopsis genome there are two orthologs of yeast SGF29, designated as SGF29a and SGF29b. We hypothesized that, in Arabidopsis, one or both SGF29 proteins may work in concert with ADA2b to regulate g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
59
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 71 publications
(98 reference statements)
4
59
0
Order By: Relevance
“…18 These results indicate that ADA2b may act as a positive regulator of salt-induced gene expression. This ADA2b's action is distinct from that of ADA2a and GCN5, since in the ada2a-2 and gcn5-1 as well as gcn5-2 mutants the expression of the stress-inducible genes was not affected by high salinity stress (Fig.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 82%
See 3 more Smart Citations
“…18 These results indicate that ADA2b may act as a positive regulator of salt-induced gene expression. This ADA2b's action is distinct from that of ADA2a and GCN5, since in the ada2a-2 and gcn5-1 as well as gcn5-2 mutants the expression of the stress-inducible genes was not affected by high salinity stress (Fig.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 82%
“…17 As a result in Arabidopsis, gcn5 mutants exhibit pleiotropic developmental defects, including dwarfism, loss of apical dominance, aberrant meristem function in root and shoot, leaf and flower development, short petals and stamens, flower infertility and plant responses to abiotic stress. 14,15,[17][18][19][20][21][22][23] Chromatin immunoprecipitation coupled with a promoter chip revealed that about 40% of the promoters are associated with the Arabidopsis GCN5 protein. 24 The GCN5 bromodomain is required for a small fraction (11%) of the AtGCN5 targets and their H3K14 acetylation.…”
Section: Histone Acetylation and Abiotic Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent report showed that ADA2b positively regulates salt-induced gene expression by maintaining the locus-specific acetylation of histones H4 and H3b. ChIP assays demonstrated that the promoter and coding regions of COR6.6 (COLD RESPONSIVE 6.6), RAB18 (RESPONSIVE TO ABA 18), and RD29b genes had reduced levels of histone H3 and H4 acetylation in ada2b-1 mutants relative to wild-type plants [ 48 Kaldis et al, 2011]. Our group has identified HAT gene homologues from barley.…”
Section: Histone Modification Enzymes Histone Acetyltransferases (Hats)mentioning
confidence: 99%